Diversity of diurnal butterflies (Lepidoptera: Papilionoidea) associated with a shade coffee agroecosystem (Curití, Santander). (2017)
Shade grown coffee crops generate environments more similar to mountain ecosystems than monocultures of coffee exposed to direct sunlight. Although butterflies are considered useful bioindicators of the state of ecosystem health, their diversity remains unknown in coffee agroecosystems in Santander, where coffee is grown under shade. The structure and composition of the assembly of the Papilionoidea in a shade coffee plantation (Hacienda La Capellanía, Curití, Santander) at an altitude of 1756 m (August-September, 2014) are described. In three parallel transects of 50 m inside the crop, nine Van Someren-Rydon traps were baited with decomposed fruit, and additional specimens were captured with an entomological net. The sampling coverage was estimated at 81.67 % (Clench equation). Overall, 341 individuals of 49 species of the family Nymphalidae (spp. = 39), Pieridae (spp. = 7), Papilionidae (spp. = 2) and Lycaenidae (sp. = 1) were captured. The most abundant species were Cissia pompilia, Graphita griphe and Hermeuptychia harmonia. Species richness (α = 16), dominance (D = 0.07), evenness (J’ = 0.81) and effective number of species (°D = 58.8, 1D = 23.73 and 2D = 14.26) were estimated. Vegetation structure was related to the composition of butterfly communities (canonical correspondence analysis). The abundance of butterflies was significantly associated with the percentage of tree cover, height, trunk diameter, and the abundance of trees in the coffee plantation. This study is one of the first to describe the diversity of butterflies associated with shade coffee in the department of Santander. Traditional shade coffee agroecosystems may benefit the diversity of butterflies because the heterogeneity of their plant structure offers a greater availability of resources and shelter for them.